Efektivitas Dan Efisiensi Penggunaan Aplikasi Backoffice Sistem Dalam Mengelola Anggaran Di BPS Kota Palu - Tiara Tiara; Vitayanti Fattah; Juliana Kadang; Anisah Anisah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to analyze the effectiveness and efficiency of using the BackOffice System (BOS) application in budget management at the Central Statistics Agency (BPS) of Palu City. The research method used is qualitative, with data collection through interviews, observation and documentation studies. The BOS application has been used at Palu City BPS since the beginning of 2023 to manage the budget. This research uses descriptive qualitative methods to analyze the effectiveness and efficiency of using the BackOffice System application in budget management at the Palu City Central Statistics Agency. Data was collected through observation, documentation, and direct interviews with key informants such as Budget User Officials, Commitment Making Officials, General Subdivisions, Treasurers, and BOS Operators. The Technology Acceptance Model (TAM) concept is used to explain the acceptance and use of technology. The research results show that the implementation of the BackOffice System (BOS) application at the Palu City Central Statistics Agency is effective in improving budget management to be more efficient. The BOS application makes access easier, makes financial management more transparent, and makes it easier to create assignment letters and complete payments. Even though there are still several shortcomings, the BOS application is considered successful in achieving its goals and has helped in budget management. Research shows that the implementation of the BackOffice System application at BPS Palu City has brought benefits in budget management, increasing the effectiveness of financial management efficiency. Nevertheless. There are still several technical obstacles that need to be overcome. The BOS application makes access easier, makes financial management more transparent, and makes it easier to create assignment letters and complete payments. Even though there are still shortcomings, the BOS application is considered successful in achieving its goals.